Interactions Of Triphenyl-Methane Compounds With Fibrinogen And Fibrin Monomers - Ryckewaert, J-J; Doolittle, R F (Thrombosis and Haemostasis, 1981)
A synthetic compound, aurin tricarboxylic acid (ATA), in the concentration range of 10-100 nanomoles/ml exhibits the property of significantly shortening the thrombin clotting time of fibrinogen. Upon binding to fibrinogen or fibrin monomers, obtained either by the action of thrombin or reptil ase on fibrinogen, ATA possesses the ability to accelerate the polymerization formation of fibrin. Polymerization studies of fibrin monomers at different ionic strengths show that ATA greatly enhances the lateral aggregation of fibrin polymers even at high ionic strength. Calcium ions do not influence the effects of ATA. Spectroscopic methods have been used to study and locate the binding sites in the different parts of the fibrinogen molecule. Compounds with structures that are closely related to that of ATA do not affect the polymerization process, with the exception of the parent compound aurin, which has a slight effect. ATA does not influence the binding ability of fibrinogen for the synthetic peptides: Gly-Pro-Arg and Gly-His-Arg, as was shown by equilibrium dialysis experiments with radioactive- labelled peptides. Nevertheless, in the presence of Gly-Pro-Arg or Gly-Pro-Arg-Pro, which are known to interfere with the polymerization of fibrin monomer, ATA becomes a potent inhibitor of the overall process of fibrin formation. This duality of behavior has permitted us to study the different steps of longitudinal and lateral association of fibrin monomers.